The effects of training volume and competition on the salivary cortisol concentrations of olympic weightlifters - Crewther, B. T.; Heke, T.; Keogh, J. W. L. (The Journal of Strength and Conditioning Research, 2011)
This study examined the effects of training volume and competition on the salivary cortisol (Sal-C) concentrations of Olympic weightlifters. Male (n = 5) and female (n = 4) Olympic weightlifters provided saliva samples across a 5-week experimental =period. The first aim was to assess the weekly effects of high (=200 sets) and low (=100 sets) training volume on Sal-C. The second aim was to compare Sal-C concentrations and 1 repetition maximum (1RM) performance during 2 simulated and 2 actual competitions. Performance was assessed using the snatch, clean and jerk, and the Olympic total lift. Data from each competition setting were pooled before analysis. There were no significant weekly changes in Sal-C levels (p > 0.05). The actual competitions produced higher (128-130%) Sal-C concentrations (p < 0.001) and superior 1RM lifts (1.9-2.6%) for the clean and jerk, and the Olympic total, than the simulated competitions (p < 0.05). Individual Sal-C concentrations before the simulated competitions were positively correlated to all of the 1RM lifts (r = 0.48-0.49, p < 0.05). In conclusion, actual competitions produced greater Sal-C responses than simulated competitions, and this appeared to benefit the 1RM performance of Olympic weightlifters. Individuals with higher Sal-C concentrations also tended to exhibit superior 1RM lifts during the simulated competitions. Given these findings, greater emphasis should be placed upon the monitoring of C to establish normative values, training standards and to assist with performance prediction.